Cybersecurity and AI: Protecting Survivors of Sexual Violence from Digital Harassment - Rawat, Shivali (Journal of Neonatal Surgery, 2025)
The rise of digital technology and artificial intelligence (AI) has led to an increase in cyber threats, particularly targeting survivors of sexual violence. Digital harassment, including cyberstalking, doxxing, deepfake abuse, and online threats, exacerbates the trauma faced by survivors and undermines their right to safety. While existing legal frameworks attempt to address these issues, rapid technological advancements often outpace regulatory mechanisms, leaving significant gaps in protection. This research paper examines the intersection of cybersecurity, AI, and legal protections to safeguard survivors of sexual violence from digital harassment. It explores the effectiveness of international and domestic laws, including the Budapest Convention on Cybercrime, GDPR, IT Act (India), and U.S. cyber laws, in addressing digital violence. The study highlights key challenges such as enforcement difficulties, cross-border jurisdiction issues, and the anonymity of digital platforms that embolden perpetrators. AI plays a dual role in this context. While it enables new forms of digital harassment through deepfakes and automated abuse, it also offers innovative solutions for identifying and mitigating online threats. AI-driven content moderation, machine learning algorithms for threat detection, and cybersecurity measures such as encryption and digital forensics are crucial tools in combating online harassment. However, concerns regarding AI bias, ethical implications, and the risk of false positives necessitate careful governance. This paper further explores the role of cybersecurity strategies in empowering survivors, emphasizing the importance of data protection laws, platform accountability, and user safety measures. It also examines best practices for integrating legal and technological solutions, ensuring a survivor-centric approach to policymaking. The study concludes by proposing legal reforms, enhanced AI governance, and international cooperation to create a robust legal framework against digital harassment. Strengthening regulatory mechanisms, ensuring ethical AI deployment, and fostering collaboration between governments, tech companies, and civil society are critical steps toward a safer digital environment. This research aims to contribute to the discourse on AI-driven cyber threats while advocating for stronger legal protections and policy interventions to support survivors of sexual violence.